Art - Bell, Clive (London Arrow, 1961)
Clive Bell was a 20th century art critic. Wikipedia summarized Bells philosophy as follows. In general formalism (which can be traced back at least to Kant) is the view that it is an object's formal properties which makes something art, or which defines aesthetic experiences. Bell proposed a very strong version of formalism: he claimed that nothing else about an object is in any way relevant to assessing whether it is a work of art, or aesthetically valuable. What a painting represents, for example, is completely irrelevant to evaluating it aesthetically. Consequently, he believed that knowledge of the historical context of a painting, or the intention of the painter is unnecessary for the appreciation of visual art. He wrote: "to appreciate a work of art we need bring with us nothing from life, no knowledge of its ideas and affairs, no familiarity with its emotions"(Bell p27). According to Bell nothing is more valuable that a visual work of art.
Keywords: Fine art